HUBUNGAN REMAJA SELAMA MENGIKUTI SEKOLAH DARING MASA PANDEMI COVID-19 DENGAN GANGGUAN KESEIMBANGAN STATIS - siti nadhir ollin norlinta (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
The development has begun to be used by several schools and universities in Indonesia as the implementation of their educational programs during the Corona Viruz Pandemic. The program is known as an online learning program or e-learning system or online learning. Currently, teenage students are required to do learning activities from home with smartphones or computers. This can potentially lead to obesity, decreased physical ability, endurance and can affect the balance of adolescents. Balance disorders for adolescents are due to non-optimal daily activities that cause muscle strength to be not optimal. This research is a type of research non-experimental, the research design used in this study is analytic observation with the measuring instrument used is the Standing Stork Test or (one-leg stand) with the subject according to the inclusion criteria. The observation uses by telehealth with respondents who will be the object of research. The purpose of this study is to find out the problems posed in adolescents associated with the online learning process during COVID-19. The results of this research that correlation coefficient of 0.015 and -0.419 in this test indicate that the reduced physical activity in adolescents will cause a decrease in the body's static balance.